Market hog price discovery - Schroeder, Ted C.; Mintert, J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Cash hog markets are declining in importance, and use of formula pricing of market hogs is increasing. Producers need more information to assist them in price discovery and formula price negotiations with pork packers. Lean hog futures and pork wholesale plus by-product values offer useful pricing information for producers. However, using these markets as sources ofprice information is not without challenges. This report highlights issues involved in hog market price discovery and examines the usefulness of lean hog futures and wholesale pork values in price discovery.
Keywords: Swine; Price discovery; Hog prices